2019
DOI: 10.1007/s11207-018-1392-4
|View full text |Cite
|
Sign up to set email alerts
|

Solar Flare Forecasting from Magnetic Feature Properties Generated by the Solar Monitor Active Region Tracker

Abstract: We study the predictive capabilities of magnetic-feature properties (MF) generated by the Solar Monitor Active Region Tracker (SMART: Higgins et al. in Adv. Space Res. 47, 2105, 2011) for solar-flare forecasting from two datasets: the full dataset of SMART detections from 1996 to 2010 which has been previously studied by Ahmed et al. (Solar Phys. 283, 157, 2013) and a subset of that dataset that only includes detections that are NOAA active regions (ARs). The main contributions of this work are: we use margina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Comparative analyses of algorithms have been used in many different application domains, see for example [31]. The success of potential approaches is domain specific and will depend on the structure of the data at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses of algorithms have been used in many different application domains, see for example [31]. The success of potential approaches is domain specific and will depend on the structure of the data at hand.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the random nature of solar flares, it is difficult to find an effective precursor. In the recent development of solar flare forecast, deep learning methods [76][77][78][79] are used to automatically extract forecasting patterns from the observational data and finally build a forecasting model. Depending on the big observational solar data, deep learning methods may be one of ways to improve Figure 4 illustrates the structure of the CNN.…”
Section: Solar Flare Forecasting Modelsmentioning
confidence: 99%
“…Recently, the application of supervised machine learning methods, especially deep neural networks (DNNs), to solar flare prediction has been a hot topic, and their successful application in research has been reported (Huang et al 2018;Nishizuka et al 2018;Park et al 2018;Chen et al 2019;Domijan et al 2019;Liu et al 2019;Zheng et al 2019;Bhattacharjee et al 2020;Jiao et al 2020;Li et al 2020;Panos & Kleint 2020;Yi et al 2020). However, there is insufficient discussion on how to develop the methods available to real-time operations in space weather forecasting offices, including the methods for validation and verification of the models.…”
Section: Introductionmentioning
confidence: 99%